Effect of Hydraulic Retention Time on Food Chain Reactor (FCR) Performance in Industrial Wastewater Treatment - Gardana, Rivelino; Mikhael, Magenta; Maulidiany, Nopa Dwi; Wandi, Asep (Syntax Literate, 2025)
Industrial estate wastewater treatment presents significant challenges due to its complex composition. Food Chain Reactor (FCR) technology has been implemented in several wastewater treatment plants (WWTPs) in industrial estates across Indonesia as a promising solution for the removal of organic compounds, nutrients, and heavy metals. However, there is limited research on the optimization of FCR performance. This study aims to evaluate the optimal hydraulic retention time (HRT) for FCR by assessing its efficiency in removing COD, ammonia, phosphate, and nickel from industrial estate wastewater. A 60 L lab-scale FCR reactor was tested under HRT variations of 12, 16, and 24 hours. The pollutant removal efficiencies ranged from 86.16% to 90.79% for COD, 77.92% to 88.96% for ammonia, 54.76% to 63.09% for phosphate, and 40.83% to 51.99% for nickel. The 12-hour HRT achieved the highest COD removal efficiency (90.79% ± 1.59%), while the variation in HRT had minimal influence on ammonia, phosphate, and nickel removal. ANOVA results confirmed a highly significant effect of HRT on COD removal (p < 0.0001), while the removal efficiencies for ammonia, phosphate, and nickel were not significantly affected (p > 0.05). These findings suggest that FCR technology is highly effective for COD removal at shorter HRTs, but further optimization is needed for more efficient removal of nutrients and heavy metals.